Parenting styles, coparenting, and early child adjustment in separated families with child physical custody processes ongoing in family court - Pires, M. (2021)
Abstract: Coparenting conflict and triangulation after separation or divorce are associated with poorer child adjustment when parenting gatekeeping and conflict occur. Fewer studies reported psychosocial adjustment of children under three. We explored the effects of authoritarian and permissive parenting styles and negative coparenting on child adjustment in a purpose sample of 207 Portuguese newly separated/divorced parents (50.2% mothers/49.8% fathers) with sole or joint (49.8%/50.2%) physical custody processes ongoing in court. Parents filled out the Parenting Styles Questionnaire—Parents’ report, the Coparenting Questionnaire, and the Strengths and Difficulties Questionnaire. Parenting and coparenting moderations path analysis to predict child adjustment were tested for two groups (2/3-year-old child/>3-year-old-child) and showed a good fit, followed by multigroup path analysis with similarities. Findings suggest harsh parenting and interparental conflict and triangulation as predictors for poor early child adjustment. The ongoing custody process could contribute to increased interparental conflict. The families’ unique functioning, parenting, and conflict should be considered in young children custody decisions made in a particularly stressful period when the parental responsibilities’ process is still ongoing and conflict may increase to serve the best interest of the child and promote healthy development. Future directions and practical implications are discussed.